Low-Temperature Carbonization on Biochar from Agricultural Waste for Heavy Metal Removal - Puari, Aninda; Yanti, Nika R. (Jurnal Keteknikan Pertanian, 2025)
Biochar from agricultural waste has many applications in the field of agricultural and wastewater treatment. In this study, biochar derived from exhausted kahwa coffee (EKC) was produced at low carbonization temperatures (200–400°C) for the removal of copper (II) ions (Cu2+) from aqueous solutions. The EKC biochar exhibited a removal efficiency of 92.5% under optimal conditions. The biochar was also subjected to surface characterization for further investigation of the varied capacity removal of the EKC biochar at low temperatures. BET analysis was performed on the EKC biochar to gather information on the surface area and pore size, and the structure of the formed pores was imaged using SEM. Furthermore, the elemental content and functional groups on the surface of the EKC biochar were determined by EDX and FT-IR analyses. The results showed that the surface and pore sizes of the EKC biochar had an interplay with the capacity removal of the EKC biochar during low-temperature carbonization. Meanwhile, it was also confirmed that the elemental ion content and the surface functional groups showed a stronger relation to the removal capacity of the EKC biochar at each low temperature applied.